The Development and Validation of Jihad Academic Scale (JAS) - M. Fadli Nugraha (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2022)
The purpose of this study was to construct and validate the jihad academic scale. Because jihad is broadly divided into major (non-physical) and minor (physical) jihad, this research focuses on the construction of the major (non-physical) jihad, which is carried out in the academic or how they strive to study in their education. The study consisted of a pilot study (n=61), a first study (n=183), and a second study (n=183), using a convenience sampling technique. A quantitative method with exploratory factor analysis (EFA) design followed by confirmatory factor analysis (CFA). Validity uses to construct convergent and discriminant validity—analysis using the JASP program. The results of the EFA study formed three dimensions. The CFA results stated that the proposed model was fit based on the CFI=0.94 (> 0.90) SRMR=0.05 (< 0.08) GFI=0.91 (> 0.90). But still not fit in accordance with p-value 2=0.01 (> 0.05) and RMSEA=0.06 (< 0.05). Then it has been reliably seen from α = 0.88 (> 0.70). Then the convergent validity is seen from the academic resilience scale with the correlation value of Pearson's (r = 0.41) and Spearman's (rho = 0.35) with each masing p-value < .001. Then, for discriminant validity, it can be seen from the school burnout inventory scale with the correlation value of Pearsons (r = - .11) with p-value=.012 and spearman's (rho = - .21) with p-value= .00438. The normality assumption of Shapiro-Wilk (W= 0.87) with p-value < .001. Overall, this scale can be used in a university environment and can then be developed at other levels of education with a larger number of samples to confirm each factor.